2016
DOI: 10.5435/jaaos-d-14-00130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Diagnosis of Back Pain in Children and Adolescents

Abstract: Although traditionally it has been accepted that back pain in young children and adolescents most often has an organic etiology, nonorganic back pain in this population is becoming more common. The most common identifiable clinical entities responsible for such pain are spondylolysis, spondylolisthesis, Scheuermann kyphosis, overuse syndromes, disk herniation, apophyseal ring fracture, spondylodiscitis, vertebral osteomyelitis, and neoplasm. Appropriate clinical workup leads to earlier diagnosis and management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…15 Recent studies 6,7 suggested that the prevalence of BP has been increasing in adolescents; this can cause a range of disabilities that may persist into adulthood. 810 Therefore, the causes of BP must be investigated with a focus on adolescents. 11 Although several recent studies examined the prevalence and risk factors of BP in adolescents, 1220 most had a cross-sectional design; thus, no causality could be established.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recent studies 6,7 suggested that the prevalence of BP has been increasing in adolescents; this can cause a range of disabilities that may persist into adulthood. 810 Therefore, the causes of BP must be investigated with a focus on adolescents. 11 Although several recent studies examined the prevalence and risk factors of BP in adolescents, 1220 most had a cross-sectional design; thus, no causality could be established.…”
Section: Introductionmentioning
confidence: 99%
“…While back pain is a common complaint among adults and older adolescents, it is uncommon in children and often reflects a pathologic condition. [32][33][34] In another case of failure to recognize a concerning presentation a 14-month-old female developed new-onset right-sided torticollis that waxed and waned over several months and was associated with frequent morning emesis. She was brought to the emergency department twice, but no imaging was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Back pain (BP), defined as "pain within the cervical, thoracic and/or lumbar areas" [1][2][3], is a significant public health problem [1][2][3][4][5][6][7]. Recent studies [8][9][10] suggest that the prevalence of BP, including acute, chronic, specific, and non-specific conditions, has been increasing among adolescents; it can cause a range of functional limitations that may persist into adulthood [11][12][13]. Therefore, the causes of BP among adolescents should be investigated [14].…”
Section: Introductionmentioning
confidence: 99%